Research progress in vaccination during pregnancy - Zhang, Jiao; Li, Zhimin; Li, Shiran; Li, Pengfei; Xie, Jingxian; Yang, Yong (Frontiers in Immunology, 2025)
Pregnant women and infants are more vulnerable to infectious diseases than the general population. Vaccination during pregnancy can protect not only mothers and fetuses from diseases but also safeguard infants through maternal antibodies transferred via the placenta. It stands as one of the most effective strategies to reduce the incidence and mortality of infectious diseases among pregnant women and infants. Globally, pregnancy vaccination strategies are increasingly diversified. This review discusses the effectiveness and safety of various vaccines for preventing infectious diseases during pregnancy, as well as vaccination recommendations for pregnant women across different countries.